1997
DOI: 10.2169/internalmedicine.36.565
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Case of Cockayne Syndrome without Sclerotic Angiopathy.

Abstract: Wereport an autopsy case of Cockaynesyndrome(CS). A40-year-old Japanese womanwas admitted to our hospital for cachexia. She had displayed the striking features of CS, including dwarfism, mental retardation, neural deafness, ataxia, intracranial calcifications, and progeria since her childhood. Endocrinological examinations suggested normal pituitary function and a disorder of the hypothalamus or the cerebrum. She died of acute pneumonia at the age of 42. Autopsy findings showed typical abnormalities in the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 9 publications
1
28
1
Order By: Relevance
“…However, the skills attained and average age at death (30.3 years) in mild CS are significantly increased over other groups. As a result, many in this group are not suspected of having CS until adulthood and/or after they have visited many physician specialists-if they are diagnosed at all [Inoue et al, 1997;Rapin et al, 2006]. The literature describes mild CS/CS in adults as atypical or rare [Kennedy et al, 1980;Nance and Berry, 1992;Rapin et al, 2006;Morris et al, 2007;Hashimoto et al, 2008], yet the even distribution of severity group membership among survey subjects here (Table I) implies that mild CS may be under-diagnosed.…”
Section: Mild Csmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the skills attained and average age at death (30.3 years) in mild CS are significantly increased over other groups. As a result, many in this group are not suspected of having CS until adulthood and/or after they have visited many physician specialists-if they are diagnosed at all [Inoue et al, 1997;Rapin et al, 2006]. The literature describes mild CS/CS in adults as atypical or rare [Kennedy et al, 1980;Nance and Berry, 1992;Rapin et al, 2006;Morris et al, 2007;Hashimoto et al, 2008], yet the even distribution of severity group membership among survey subjects here (Table I) implies that mild CS may be under-diagnosed.…”
Section: Mild Csmentioning
confidence: 85%
“…Males (n ¼ 11), averaged 131 cm (50th centile for age 8 1 / 2 years) [Smits et al, 1982;Fryns et al, 1991;Nance and Berry, 1992;Miyauchi et al, 1994;Ellaway et al, 2000;Komatsu et al, 2004]. Females (n ¼ 8) averaged 127 cm (50th centile for age 8 years) [Brumback et al, 1978;Kennedy et al, 1980;Miyauchi et al, 1994;Inoue et al, 1997;Lahiri and Davies, 2003;Hashimoto et al, 2008].…”
Section: Fig 2 Patient 2 Very Mildmentioning
confidence: 99%
“…Thorough endocrine investigation in case 3 23 indicated that pituitary function, including growth hormone levels and response, was normal. It was suggested that the basis of endocrine disturbance, in particular the ubiquitous hypogonadism, might be hypothalamic.…”
Section: Endocrine Statusmentioning
confidence: 99%
“…Egly (quoted in Bohr et al 35 ) reported that mutation of XPD indirectly lowers the expression of reporter genes regulated by vitamin D, retinoic acid, and estrogen. It is also not clear whether the prominent joint contractures in cases 3, 23 5, 6 6, and 13 were caused by spasticity, neuropathic weakness, limited mobility, osteoporosis with degenerative changes in the spine and articulations, or all of them. Cases 5 6 and 6 were bald in their early thirties, and thinning of the hair is mentioned in many of the reports.…”
Section: Premature Aging and Cardiovascular Diseasementioning
confidence: 99%
“…A literature review returned only five cases of CS with diabetes, from which four were reported in Japan (3)(4)(5).…”
mentioning
confidence: 99%